Level shifter signal conditioning circuit design for 3-electrode cell portable redox sensor / Nur Rabi'atul 'Adawiyah Muhd Zain ... [et al.] - Muhd Zain, Nur Rabi'atul Adawiyah; Nordin, Zatieyl Aqmar; Rosli, Aimi Bazilah; Abdullah, Wan Fazlida Hanim (UiTM Press, 2023)
This paper presents the effect of level shifter signal conditioning circuits in a low-cost portable potentiostat, implemented by combining several circuit modules and controlled by Advanced RISC Machines Cortex processor. Two architectures of level shifter modules are simulated: Non-inverting Summing Amplifier and Inverting Summing Amplifier. The main objective is to improve signal detection readability by widening the input voltage signal processing and increasing the amplitude range of the sensor output signal before the analog to digital signal conversion. The potential amplitude range of redox reaction captured by trans-impedance module at -3 V to 3 V is reduced by 50%. Then, the output voltage is converted by analog digital converter to be interfaced with microcontroller for Differential Pulse Voltammetry current properties. The designed potentiostat has a current readout range of ± 500mA and is validated to be at 15% difference with the standard laboratory potentiostat.